THE IMPORTANCE OF IRON DEFICIENCY ANEMIA PREVENTION FOR PREGNANT WOMEN’S HEALTH - Mutabar Abduganievna Mirpaizieva (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Anemia is a pathological condition characterized by a decrease in hemoglobin concentration and, in the vast majority of cases, the number of red blood cells per unit volume of blood. Iron deficiency anemia (IDA) is a disease of global significance, affecting 2 billion people (30% of the world’s population). Iron deficiency affects more people than any other health condition, making it a major public health problem. Iron deficiency anemia (IDA) is the most common deficiency and the most common form of anemia in pregnant women. The problem of iron deficiency disorders (IDD) and iron deficiency anemia (IDA) remains a pressing issue. Its clinical implications are extremely important, as the adverse effects of iron deficiency not only affect the woman’s body but can also impact pregnancy outcomes and the health of newborns.